The Doctrine of Promissory Estoppel: As a Shield or Sword? - Mohd Angsor, Mohd Asmadi; Adi, Nazir (Research in Management of Technology and Business, 2020)
Promissory estoppel is a reasonable doctrine arising from the rule of equiy where the principle of good faith is not accepted by common law as part of the law concerning contractual transactions. It is an equitable principle meant to prevent any accurance of inequity or injustice caused by the action of the promisor in backing out from his promise, which initially led the promisee to act to his detriment. This concept paper discuss the basic principle of promissory estoppel with referrance on the land mark cases for better understanding towards its applicability in business transaction particularly in the contract transaction. It is not a sword, but a shield. It may not be used as a cause of action in English law as it can only be used as a defensive mechanism to safeguard anyone who may face arbitrary enforcement of strict legal rights. Promissory Estoppel is an advanced doctrine for 'Stop' people from taking that right he has promised to exclude or waiver, or neglect to make a correct statement or fail to present correctly when such change occurs which affects his ability to fulfil the promise or part of it.